Evaluation of Coal Supplied to Soma Thermal Power Plant (Türkiye) with Statistical Process Control Techniques - Sedat Toraman; Mehmet Taksuk; Cem Şensöğüt (International Journal of Economic and Environment Geology)
Statistical Process Control (SPC) is a method developed to ensure that production activities are carried out in accordance with predetermined quality specifications and to minimize the production of defective products/goods by largely preventing non-standard production.Various scientific methods are used when the calorific values of coal fed to thermal power plants are examined in terms of quality. In this study, the calorific values and other specifications of the coal fed to the Soma Thermal Power Plant (Manisa/Türkiye) and whether the process is under control or not are examined by consideringthe two-year data for tracking and monitoring the process with the Statistical Process Control (SPC) method, taking into account both the design conditions of the power plant and the production parameters. The adequacy of the processes for which stabilityanalysis was performed was evaluated in the next stage.When the two-year control charts (𝑋̅and R) of units 1-4 and unit 5-6 in the power plant were examined, it was determined that although the process was generally under control in terms of 10-day homogeneity, there were abnormal behaviors showing specific reasons in the 𝑋̅chart. Therefore, the process that feeds coal to groups 1-4 and 5-6 of the power plant for the two years in question is unstable. It was also concluded that the process was insufficient to meet the calorific value limits specified on an annual basis.